2016
DOI: 10.1038/srep25561
|View full text |Cite|
|
Sign up to set email alerts
|

The impact of working memory and the “process of process modelling” on model quality: Investigating experienced versus inexperienced modellers

Abstract: A process model (PM) represents the graphical depiction of a business process, for instance, the entire process from online ordering a book until the parcel is delivered to the customer. Knowledge about relevant factors for creating PMs of high quality is lacking. The present study investigated the role of cognitive processes as well as modelling processes in creating a PM in experienced and inexperienced modellers. Specifically, two working memory (WM) functions (holding and processing of information and rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…The empirical assessment of participants' mental effort, while creating or comprehending process models, is demonstrated in [35]. The mental effort needed between inexperienced and experienced modelers to create process models is investigated in [36]. Altogether, there are several works regarding the comparison of process modeling notations.…”
Section: Related Workmentioning
confidence: 99%
“…The empirical assessment of participants' mental effort, while creating or comprehending process models, is demonstrated in [35]. The mental effort needed between inexperienced and experienced modelers to create process models is investigated in [36]. Altogether, there are several works regarding the comparison of process modeling notations.…”
Section: Related Workmentioning
confidence: 99%
“…For example, [24] showed that the presence of prior domain knowledge facilitates the creation of an internal representation of the process to be modeled and is associated with shorter initial comprehension phases. Moreover, Martini et al [25] showed that inexperienced modelers had significantly more comprehension and modeling phases when compared to more experienced modelers. The drawback of relying on detected modeling behavior is, however, its tool dependence (R4).…”
Section: Classifying Modelers: Requirements and Design Considerationsmentioning
confidence: 99%
“…These works, however, typically focus solely on the final outcome of the act of modeling, without considering the process of creating the process model. Instead, a more recent research field is investigating the process of process modeling (PPM): in this case the emphasis is on the process underlying the creation of process models [5,6,7,8,9,10]. The creation of a process model, starting from a domain description, subsumes the execution of several activities.…”
Section: Introductionmentioning
confidence: 99%